Cementation of rhodium from waste chloride solutions using copper powder - AKTAŞ, SERDAR (ELSEVIER SCIENCE BV, 2012)
This work investigated the cementation of rhodium from waste chloride solutions using metallic copper powder. The effects on the rhodium precipitation (%) caused by the quantity of copper, reaction temperature and reaction time were explored in detail. In addition, the cementation kinetics of rhodium were studied, and the activation energy was determined to be 64.48 kJ/mol, which indicates that the reaction is chemically controlled. It was demonstrated that less than 40% of the rhodium could be precipitated using excessive quantities of copper powder (e.g., stoichiometric ratio of Cu/Rh = 40.3) at room temperature for 1 h, which resulted in a cementation reaction that was too slow. Increasing the reaction temperature to 55 degrees C resulted in almost 99% cementation after 1 h, even using stoichiometric ratio of Cu/Rh = 16.1. After a detailed observation of the dissolution behavior of the copper powder during the cementation process, it was demonstrated that most of the copper is preferentially consumed by free acid, a finding corroborated by pH measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Rhodium; Copper; Cementation; Waste plating solutions; OXIDE BUTTON CELLS; SILVER RECOVERY; HYDROMETALLURGY